DISCUSSION ON DISEASES OF NOT LEARNIN THE INCLUSIVE EDUCATIONAL CONTEXT: WHAT DO EARLY CHILDHOOD EDUCATION TEACHERS SAY? - Mosca Giroto, Claudia Regina [UNESP]; Araujo, Luciana Aparecida de [UNESP]; Frigieri de Vitta, Fabiana Cristina [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
Due to the excessive increase of referrals and diagnoses that result in diseases of not learn, this study aimed to understand how five teachers who teach kindergarten classes, in a municipal Early Childhood Education school, discourse the diseases doen learning and the possible implications in their teaching practice. The data generation was based on the dialogue undertaken in a virtual discussion forum, which data indicated axes of analysis focused on the conceptions about diseases of not learn and the teaching practice of such diseases. The statements generated revealed the thinking and action of these teachers submitted to the medical logic, in the detriment valuation of inherent differences to the heterogeneity in Early Childhood Education.
Keywords: Inclusion; Early childhood education; Diseases doen learning; Teacher training